Peran Guru Dalam Mengidentifikasi Kecerdasan Majemuk Anak Usia Dini di PAUD - Dinda Salsabila; Faisa Rahma Safira Siregar; Najwa Dwi Aprillia; Putri Amelia; Fauziah Nasution (Journal of Cultural Relativism (JCR), 2025)
This study aims to describe the role of teachers in identifying multiple intelligences of early childhood at An-Nida Kindergarten, Jalan Mister No. 21, Sei Putih, Medan Petisah District, Medan City. This study uses a qualitative approach with a descriptive method. The subjects of the study were group B teachers who taught 15 children (10 girls and 5 boys). Data collection techniques included observation, interviews, and documentation. The results of the study showed that teachers had a fairly good understanding of the theory of multiple intelligences developed by Howard Gardner. Teachers carried out the process of identifying intelligence through observation of children's activities, analysis of work, dialogue with children and parents, and recording in a development journal. The intelligences identified included musical, kinesthetic, visual-spatial, interpersonal, logic-mathematical, linguistic, and naturalist. Teachers played an active role in following up on the identification results by providing learning stimulation that was in accordance with the child's potential. However, there were several obstacles in the identification process, such as limited measuring instruments, time, and in-depth training. This finding confirms that the role of teachers is very important in recognizing the intelligence potential of early childhood as a basis for developing holistic and child-centered learning.